Exploratory investigation of dose calculation and tumor-feeding artery identification using dual CBCT in selective internal radiation therapy with Yttrium-90 microspheres - Guo, Zhaoxiong; Liang, Yuchan; Li, Tingfeng; Li, Ao; Zhu, Kangshun; Guo, Yongjian; Wang, Wenxin; Huang, Wensou (Frontiers in Oncology, 2025)
AIMTo explore the preliminary application of dual cone-beam CT (CBCT) for dose calculation and tumor-feeding arteries identification in 90Y-SIRT planning.Materials and MethodsA retrospective study analyzed 27 patients with unresectable primary/metastatic liver tumors eligible for 90Y-SIRT. Prior to angiography, dual CBCT and 99mTc-MAA injection, each patient underwent CTA scan. Tumor volume (TV) and liver lobe volume (LLV) were measured from CTA and dual CBCT images (TVcta vs TVcbct and LLVcta vs LLVcbct). Liver perfusion volume (LPV) was derived from 99mTc-MAA mapping and dual CBCT (LPVmma vs LPVcbct). Additionally, analyze the differences between an average calculated 90Y dosage derived from TVcbct and LPVcbct, and dosage calculated using TVcbct combined with LPVmma, against the mean clinically administered (Radioactivity). The Paired Wilcoxon test was applied to evaluate differences between these parameters throughout the study.ResultsThere were no significant differences in liver tumor and perfusion volume measurements (p-values of 0.792 and 0.084, respectively). There was a significant difference in LVcbct compare to LVcta (2083.88 ± 744.64 vs 2187.86 ± 807.28 cm³, p = 0.024), which may be due to differences in contrast agent delivery. No significant differences were found among the three methods of calculated 90Y dosage(TVcbct + LPVcbct, TVcbct +LPVmma, radioactivity)were (1.819 ± 1.241, 1.806 ± 1.240, 1.805 ± 1.236)(all P>0.05).ConclusionDual CBCT is a reliable alternative to the conventional method, while offering real-time procedural advantages for feeder artery identification and catheter positioning during 90Y-SIRT.